Social security as a buffer: examining the relationship between economic policy uncertainty and rural consumption - Renxing Chen; Yu Hu; Yixin Xue; Xiaotian Zhang (Humanities & Social Sciences Communications)
Abstract Social security serves as a crucial mechanism for income redistribution and significantly shapes rural residents’ consumption patterns. Using panel data from 31 Chinese provinces (2000–2021), this study employs fixed-effects and threshold models to examine how economic policy uncertainty (EPU) affects rural consumption, with a particular focus on the dual role of social security. Key findings reveal the following: (1) EPU stimulates essential consumption but suppresses discretionary consumption among rural residents; (2) social security levels significantly mediate the EPU-consumption relationship; and (3) threshold analysis reveals nonlinear dynamics—the positive marginal effect of EPU on consumption progressively diminishes as social security levels increase. These findings advance the theoretical understanding of EPU transmission mechanisms while providing policymakers with evidence to optimize social security systems to stabilize rural household consumption.